Integration of Rasayana therapy with chemotherapy improved therapeutic outcomes in a geriatric advanced nonresponsive pancreatic cancer patient - A case report - Yogesh Narayan Bendale; Poonam Birari-Gawande; Anandrao Patil; Avinash Kadam (Wolters Kluwer Medknow Publications, 2023)
Pancreatic cancer carries one of the most dismal prognoses. In patients, who are inoperable, the main objectives of palliation are relief from obstructive jaundice, prevention or respite from gastrointestinal obstruction, and management of pain. In the present case, the patient has not shown a satisfactory response to chemotherapy, and therefore, opted Ayurveda as integrative medicine. The treatment was initiated with herbo-mineral Rasayana formulations along with chemotherapy. These therapies have significantly reduced the symptoms in the patient and also improved the quality of life (QoL). Besides improving the QoL, this case demonstrates a very important finding that combination treatment with Rasayana therapy has the potential to cause regression of tumor metabolic activity in those patients who do not respond satisfactorily to cytotoxic regimens. Besides this, Rasayana therapy also helped in improving the health-related QoL, alleviating disease symptoms, as well as toxic manifestation of chemotherapy.